2005
DOI: 10.1590/s0100-84042005000100011
|View full text |Cite
|
Sign up to set email alerts
|

Gradiente litorâneo-limnético do fitoplâncton e ficoperifíton em uma lagoa da planície de inundação do Rio Mogi-Guaçu

Abstract: -(Phytoplankton and phycoperiphyton littoral-limnetic gradient of in an oxbow lake of Mogi-Guaçu River floodplain). Study aimed at evaluating the phytoplankton and phycoperiphyton structure and dynamics during a hydrological cycle at the littoral-limnetic gradient in the Diogo Pond, and oxbow lake of the Mogi-Guaçu river floodplain (São Paulo State, Brazil). Samplings were carried out during one hydrological cycle (high water, flooding, low water, and drought) in three sites (open water, littoral-limnetic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 15 publications
2
10
0
17
Order By: Relevance
“…High loads of external material from the drainage basin are introduced into the river system during rains, especially in habitats with more intensive water exchange. Similar findings are reported for floodplains (Oliveira and Calheiros, 2000;Taniguchi et al, 2004Taniguchi et al, , 2005.…”
Section: Discussionsupporting
confidence: 89%
“…High loads of external material from the drainage basin are introduced into the river system during rains, especially in habitats with more intensive water exchange. Similar findings are reported for floodplains (Oliveira and Calheiros, 2000;Taniguchi et al, 2004Taniguchi et al, , 2005.…”
Section: Discussionsupporting
confidence: 89%
“…The organisms pertaining to this class are frequently found in warm, stable waters with low flow rates (Biggs & Kilroy, 2000). Taniguchi et al (2005) found that Oedogoniophyceae species grow at a high density on the petioles of the aquatic macrophyte Eichhornia azurea (Swartz) Kunth, attributing this to their high capacity to adhere to that substrate. In our study, the substrates available for periphytic colonization were the petioles of the aquatic macrophyte Polygonum punctatum, which possess a three-dimensional structure similar to that of the petioles of Eichhornia azurea, corroborating the findings of Taniguchi et al (2005).…”
Section: Variablementioning
confidence: 99%
“…Nevertheless, this process leads to an improvement in feeding conditions and available food sources for P. lineatus juveniles. However, the production of periphyton in the floodplains was reported as higher in receding waters and during drought periods (Taniguchi et al, 2005;Algarte et al, 2006;Carapurnarla et al, 2014) or in the Winter (Camargo & Ferragut, 2014), which also favors the bioavailability for this species.…”
Section: Discussionmentioning
confidence: 99%